2018
DOI: 10.1259/bjr.20170927
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of 90-kVp low-tube-voltage carotid and intracerebral CT-angiography: effects on radiation dose, image quality and diagnostic performance for the detection of carotid stenosis

Abstract: 90-kVp carotid and intracranial CTA with Admire provides increased quantitative and similarly good qualitative image quality, while reducing radiation exposure substantially compared to M_0.6. Diagnostic performance for arterial stenosis detection and quantification remained excellent. Advances in knowledge: 90-kVp carotid and intracranial CTA with an advanced iterative reconstruction algorithm results in excellent image quality and reduction of radiation exposure without limiting diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…5 Some recent studies suggested the use of low tube voltages for singleenergy CTA (low-kV SEI) 6 because low-kV SEI increases the CT attenuation and contrast-to-noise ratio (CNR) in structures containing iodine 7 and is associated with less radiation dose. 8,9 With the introduction of dual-energy CT (DECT), further alternatives to improve iodine attenuation and to decrease radiation dose have become clinically available. Here, second-generation virtual monoenergetic images (VMIs+) reconstructed from DECT improve the CNR of iodine at low-keV levels by combining the high signal at lower energies with the noise properties at medium energies.…”
mentioning
confidence: 99%
“…5 Some recent studies suggested the use of low tube voltages for singleenergy CTA (low-kV SEI) 6 because low-kV SEI increases the CT attenuation and contrast-to-noise ratio (CNR) in structures containing iodine 7 and is associated with less radiation dose. 8,9 With the introduction of dual-energy CT (DECT), further alternatives to improve iodine attenuation and to decrease radiation dose have become clinically available. Here, second-generation virtual monoenergetic images (VMIs+) reconstructed from DECT improve the CNR of iodine at low-keV levels by combining the high signal at lower energies with the noise properties at medium energies.…”
mentioning
confidence: 99%
“… 5 As such, the occurrence of lacunar strokes is much more common in NS compared with territorial infarcts. 4 , 5 , 16 , 17 As noted in P12, large vessel involvement may also be seen with leptomeningitis secondarily involving the vessel wall. In our cases with vessel wall enhancement, there was no intraluminal thrombus, significant stenosis, or presence of larger infarcts in the involved vascular territory.…”
Section: Discussionmentioning
confidence: 78%
“…This was noticed in our recent paper with increased image noise in the 70 kVp protocol with a pitch of 3.2 affecting visualization of thrombus and pulmonary arterial wall (25). With the latest CT scanners, advanced IR algorithms are developed to improve image quality by reducing image noise associated with the use of low-dose CT protocols (27,28). This is confirmed by findings in our study as the IR available with the Siemens Force scanner represents the latest algorithm used in image reconstruction for reducing image noise.…”
Section: Discussionmentioning
confidence: 99%